Cephalometric Study of the Overjet Development in Warmblood Foals - Domanska-Kruppa, Natalia; Venner, Monica; Bienert-Zeit, Astrid (Frontiers in Veterinary Science, 2019)
Class II dental malocclusion is the most frequently occurring congenital malocclusion in horses. Cephalometric procedures adopted from human dentistry were used to study the development of overjet in a population of 650 warmblood foals. Thirteen foals were diagnosed with measurable overjet at the beginning of the study. The malocclusion in nine foals resolved spontaneously and four foals without overjet at the time of birth developed the condition during the first year of life. A cephalostat used in human orthodontics to immobilize patient’s head while being radiographed was replaced by a researcher-made head-holding device, whose size was based on the results of preliminary research. Laterolateral digital radiographs of each foal’s head (cephalograms) were taken at five time points until the age of 12 months. Thirteen cephalometric points were identified and nine distances were measured on each radiograph. Additionally, the angle between the long axis of the upper and lower incisors was evaluated. Cephalometric measurements proved to be useful to identify foals that showed spontaneous regression of the malocclusion over the study time between 9 and 16 weeks of age.